Effect of Aloe Vera Gel on prevention of Striae Gravidarum - Sahar Bagherian; Sedigheh Amir Ali Akbari; Nourossadat Kariman; Zahra Lorigooini; Maliheh Nasiri (Mashhad University of Medical Sciences, 2021)
Introduction: Striae Gravidarum is a skin physiological change in purple that many women experience during pregnancy and due to the accompanying problems, they suffer from stress and worries about beauty, low self-esteem and psychological problems. This study was performed with aim to determine the effect of aloe vera gel on prevention of striae gravidarum in nulliparous pregnant women. Methods: This triple-blind randomized clinical trial study with a control group was performed in 2019 on 90 nulliparous women with gestational age of 18-20 weeks referring to the selected centers affiliated to Shahid Beheshti University of Medical Sciences in Tehran. The subjects were randomly assigned to one of the three groups of aloe vera gel or placebo. The participants receiving aloe vera gel and placebo group daily massaged 3 cm of the gel for 2 minutes on the entire abdomen for 8 weeks, and the control group did not use any substances on the skin of the abdomen. After 8 weeks, the severity of striae was assessed by the Davy method, the severity of pruritus by the Kamini method, and the severity of the erythema by the Atwal method. Data were analyzed by SPSS software (version 20) and Kruskal-Wallis statistical test. P <0.05) was considered statistically significant.   Results: Three groups were not significantly different in terms of background and interventional variables at the beginning of the study (p >0.05). Kruskal-Wallis statistical tests showed that the incidence of striae (p = 0.001), the severity of pruritus and erythema (p = 0.001) at 28th weeks of pregnancy was significantly lower in the Aloe Vera gel group than the other two groups. Also, the chance of increasing the severity of striae in the placebo group and the aloe vera gel group were 75% and 95% lower than the control group, respectively. Conclusion: Aloe vera gel has an effect on preventing striae gravidarum and reducing itching and erythema. Aloe vera gel can be recommended to pregnant women as a low-cost method for preventing striae gravidarum.